Disputes, debt and equity - Alfred J. M. Duncan; Charles Nolan (Theoretical Economics, 2019)
We show how the prospect of disputes over firms' revenue reports promotes debt financing over equity. This is demonstrated in a costly state verification model with a risk averse entrepreneur. The prospect of disputes encourages incentive contracts that limit penalties and avoid stochastic monitoring, even when the lender can commit to stochastic monitoring. Consequently, optimal contracts shift from equity toward standard debt. In short: When audit signals are weakly correlated with true incomes, standard debt contracts emerge as optimal; if audit signals are highly correlated with true incomes, optimal contracts resemble equity. When audit costs are sufficiently high, stochastic monitoring may be optimal. Optimal standard debt contracts under imperfect audits are shown to reproduce key empirical facts of US firm borrowing.
Keywords: D52; D53; D82; D86; 330; Microeconomics; costly state veriﬁ cation; external ﬁ nance; leverage